IDENTIFICATION OF PLANT GROWTH PROMOTING PROPERTIES OF BACTERIA ISOLATED FROM WATER HYACINTH (Eichhornia Crassipes) ROOTS - Putri, Theodora Mega; Tambun, Rizka Arta Rossa; Martgrita, Merry Meryam (Universitas Medan Area, 2025)
Plant growth-promoting bacteria (PGPB) play an important role in enhancing plant growth and productivity through various biological mechanisms, such as phosphate solubilization and nitrogen fixation. This study aims to isolate and identify PGPB from the roots of water hyacinth (Eichhornia Crassipes) growing in Lake Toba, and to evaluate its potential in supporting the growth of lettuce (Lactuca sativa). Three rhizosphere bacteria were obtained and identified morphologically and biochemically as Bacillus thuringiensis (EGR1), Bacillus megaterium (EGR2), and Azotobacter vinelandii (EGR3). All three isolates showed the ability to solubilize phosphate, while only EGR3 was able to fix nitrogen. Bioassay tests using lettuce showed that EGR2 increased plant height, while EGR3 significantly increased fresh weight, number of leaves, and length of roots. These findings indicate the potential of EGR3 as a promising natural biofertilizer candidate to support sustainable agriculture.